Implementation of the Policy on the Use of the BKN e-Performance Application in the Southeast Minahasa Regency Government Environment - Mokosolang, Merry Natalia; Tasik, Femmy C M; Egeten, Maxi M (Journal of Public Representative and Society Provision, 2024)
The use of the e-Performance application will result in effectiveness and efficiency in ASN performance reporting. ASN employees no longer need to print their monthly performance results but can be directly entered into the application and can be directly assessed by the assessor without being limited by time, can be done anywhere and anytime. This study aims to determine what factors are the causes of the failure to implement the BKN e-Performance Application in the Southeast Minahasa Regency Government properly. Qualitative design was used in this study. The Human Resources Development and Personnel Agency as the research location. The focus of the study is based on aspects of communication, resources, attitudes of implementers and bureaucratic structure. Data analysis through the stages of data reduction, data presentation and preparation of conclusions and verification. The findings of the study were miscommunication in ASN in translating socialization materials, inadequate internet facilities, ASN who were still indifferent in reporting their monthly performance, and there were no standard binding rules regarding awards and sanctions regarding the use of the BKN e-Performance application for ASN.